Empowering understanding: navigating consent to ketamine treatment in adolescent mental health - Sathappan, Aakash; Yudkoff, Benjamin (Frontiers in Psychiatry, 2024)
The rising prevalence of mental health disorders in adolescents, compounded by treatment resistance, underscores the need for innovative interventions. Ketamine, recognized for its rapid antidepressant and anti-suicidal effects in adults, has recently emerged as a potential treatment for adolescents with treatment-resistant depression and suicidality. This paper aims to highlight key elements of the informed consent process, including obtaining parental consent and adolescent assent, and discussing the nature of ketamine treatment, its benefits, and potential risks. Obtaining informed consent for ketamine treatment in this demographic poses unique challenges. During the informed consent process, clinicians should balance an adolescent's growing autonomy with parental consent and address the distinct features of treatment, including ketamine's potential to induce psychedelic-like effects. Additionally, clinicians should highlight the "off-label" use in this population and the uncertainty inherent to treatment at this time, including the lack of data on repeated ketamine exposure on the developing brain. This paper also addresses challenging scenarios related to informed consent for this treatment, such as instances when parents are willing to consent but the adolescent refuses. Alternative treatment strategies such as transcranial magnetic stimulation (TMS) and electroconvulsive therapy (ECT) are also considered. In conclusion, while an emerging body of evidence suggests that ketamine shows potential for the acute treatment of adolescents with severe depression and suicidality, adherence to informed consent principles is paramount to ensure best clinical practices and uphold ethical standards amidst the current landscape of ongoing research.